The politics of Mexican development, by Roger D. Hansen (1971) ; Mexican democracy : a critical view, by Kenneth F. Johnson (1971) ; Ideología y praxis política de Lázaro Cárdenas, por Tzvi Medin (1972) - Madden, Paul (Estudios Internacionales, 1972)
-